2023
DOI: 10.1115/1.4062889
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Source Olfactory Display to Add the Sense of Smell to the Metaverse

Abstract: As the Metaverse gains popularity due to its use in various industries, so does the desire to take advantage of all its potential. While visual and audio technologies already provide access to the Metaverse, there is increasing interest in haptic and olfactory technologies, which are less developed and have been studied for a shorter time. Currently, there are limited options for users to experience the olfactory aspect of the Metaverse. This paper introduces an open-source kit that makes it simple to add the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Olfaction, as an innate sensation, plays a vital role in human interaction with the surrounding environment associating with the cerebral limbic system processing emotions, recognition, and memories. As odor recognition can be achieved with relatively minor cognitive efforts and conscious attempts through olfactory sense, external information is able to be obtained efficiently without the aid of visual and audio perception. , In addition, it is reported that olfaction is possible to be used as a complementary module for providing additional information (olfactory cues) to enhance learning, memory, and comprehension in education and life for deaf-blind individuals, such as identifying people, spaces, objects, and activities. Compared to the conventional alternatives with a great command of languages in terms of delivering complex and customized messages, ,, as the olfaction interfaces are in the early stage, they are limited by the number of smells that can be accurately discriminated. , Accordingly, recently, a number of studies have been conducted on olfactory technologies for enhancing performance and increasing the number of firmly detectable odors. , Furthermore, the olfaction interface provides undirectional and regional propagation, which enables noncontact and wireless communication and one-to-multiple crosstalk, unlike the aforementioned alternatives. Despite their high potentiality, to date, olfaction systems where most modalities are built on rigid and bulky platforms still have critical flaws, hindering them from being widely applied for aiding deaf-blind patients, including (1) inaccurate control of odor generation that harshly decreases the recognition rate and (2) bulky size and rigidity restraining them from long-term wearability and real-time wireless message delivery. , Therefore, to overcome the mechanical mismatches and increase the accuracy of the control and recognition rate, a flexible and wearable form factor, which has mechanical and physical characteristics including light weight, bendability, twistability, stretchability, and ultrathin thickness for the olfaction interfaces has been suggested for enabling long-term wearable application with a prompt response to external input. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfaction, as an innate sensation, plays a vital role in human interaction with the surrounding environment associating with the cerebral limbic system processing emotions, recognition, and memories. As odor recognition can be achieved with relatively minor cognitive efforts and conscious attempts through olfactory sense, external information is able to be obtained efficiently without the aid of visual and audio perception. , In addition, it is reported that olfaction is possible to be used as a complementary module for providing additional information (olfactory cues) to enhance learning, memory, and comprehension in education and life for deaf-blind individuals, such as identifying people, spaces, objects, and activities. Compared to the conventional alternatives with a great command of languages in terms of delivering complex and customized messages, ,, as the olfaction interfaces are in the early stage, they are limited by the number of smells that can be accurately discriminated. , Accordingly, recently, a number of studies have been conducted on olfactory technologies for enhancing performance and increasing the number of firmly detectable odors. , Furthermore, the olfaction interface provides undirectional and regional propagation, which enables noncontact and wireless communication and one-to-multiple crosstalk, unlike the aforementioned alternatives. Despite their high potentiality, to date, olfaction systems where most modalities are built on rigid and bulky platforms still have critical flaws, hindering them from being widely applied for aiding deaf-blind patients, including (1) inaccurate control of odor generation that harshly decreases the recognition rate and (2) bulky size and rigidity restraining them from long-term wearability and real-time wireless message delivery. , Therefore, to overcome the mechanical mismatches and increase the accuracy of the control and recognition rate, a flexible and wearable form factor, which has mechanical and physical characteristics including light weight, bendability, twistability, stretchability, and ultrathin thickness for the olfaction interfaces has been suggested for enabling long-term wearable application with a prompt response to external input. …”
Section: Introductionmentioning
confidence: 99%
“…22,33 Accordingly, recently, a number of studies have been conducted on olfactory technologies for enhancing performance and increasing the number of firmly detectable odors. 34,35 Furthermore, the olfaction interface provides undirectional and regional propagation, which enables noncontact and wireless communication and one-to-multiple crosstalk, unlike the aforementioned alternatives. Despite their high potentiality, to date, olfaction systems where most modalities are built on rigid and bulky platforms still have critical flaws, hindering them from being widely applied for aiding deaf-blind patients, including (1) inaccurate control of odor generation that harshly decreases the recognition rate 36 and (2) bulky size and rigidity restraining them from long-term wearability and realtime wireless message delivery.…”
Section: Introductionmentioning
confidence: 99%